SIRT7 facilitates endometrial cancer progression by regulating PTEN stability in an estrogen-dependent manner - Zhiyi Hu; Ming Tang; Yujia Huang; Bailian Cai; Xiaoxiang Sun; Guofang Chen; Ao Huang; Xiaoqi Li; Ab Rauf Shah; Lijun Jiang; Qian Li; Xianghong Xu; et al. (Nature Communications)
Abstract The prognosis of metastatic endometrial carcinoma (EC), one of the most common gynecological malignancies worldwide, remains poor, and the underlying driver of metastases is poorly understood. Dysregulation in estrogen-related signaling and inactivation of tumor suppressor PTEN are two essential risk factors of EC. However, whether and how they are interconnected during EC development remains unclear. Here, we demonstrate that the deacetylase SIRT7 is upregulated in EC patients and mouse models, facilitating EC progression in vitro and in vivo. Mechanistically, in an estrogen-dependent fashion, SIRT7 mediates PTEN deacetylation at K260, promoting PTEN ubiquitination by the E3 ligase NEDD4L, accelerating PTEN degradation and, consequently, expediting EC metastasis. Additionally, SIRT7 expression strongly correlates with poor survival in EC patients with wild-type PTEN, though no significant correlation is observed in PTEN mutation patients. These results lay the foundation for the study of targeting estrogen-SIRT7-PTEN axis, to restore PTEN abundance, offering potential avenues for EC therapy.